Cell-Based Radiotracer Binding and Uptake Inhibition Assays: A Comparison of In Vitro Methods to Assess the Potency of Drugs That Target Monoamine Transporters - Ilic, Marija; Maier, Julian; Holy, Marion; Jaentsch, Kathrin; Liechti, Matthias E.; Lubec, Gert; Baumann, Michael H.; Sitte, Harald H.; Luethi, Dino (Frontiers in Pharmacology, 2020)
High-affinity monoamine transporters are targets for prescribed medications and stimulant drugs of abuse. Therefore, assessing monoamine transporter activity for candidate medications and newly-emerging drugs of abuse provides essential information for industry, academia, and public health. Radiotracer binding and uptake inhibition are the gold standard assays for determining drug-transporter interaction profiles. The combined results from such assays yield a unique biochemical fingerprint for each compound. Over time, different assay methods have been developed to assess transporter activity, and the comparability of data across various assay platforms remains largely unclear. Here, we compare the effects of six well-established stimulants in two different cell-based uptake inhibition assays, one method using adherent cells and the other using suspended cells. Furthermore, we compare the data from transfected cell lines derived from different labs and data reported from rat synaptosomes. For transporter inhibitors, IC50 values obtained by the two experimental methods were comparable, but using different transfected cell lines yielded disparate results. For transporter substrates, differences between the two cell lines were less pronounced but the drugs displayed different inhibition potencies when evaluated by the two methods. Our study illustrates the inherent limitations when comparing transporter inhibition data from different laboratories and stresses the importance of including appropriate control experiments and reference compounds when investigating new drugs of interest.